Pengaruh Kecanduan Game Online terhadap Konsentrasi Belajar Peserta Didik di SMP Negeri 2 Ampek Nagari Kabupaten Agam - Anisa Marta Yunas; Mori Dianto; Yasrial Chandra (Journal on Education, 2023)
This research is motivated by the influence of online game addiction on the learning concentration of students at SMP Negeri 2 Ampek Nagari Kababupaten Agam. The purpose of the research is to describe; 1) Knowing the description of online game addiction at SMP Negeri 2 Ampek Nagari, Agam Regency. 2) Knowing the description of students' learning concentration at SMP Negeri 2 Ampek Nagari, Agam Regency. 3) Knowing the effect of online game addiction on learning concentration at SMP N 2 Ampek Nagari, Agam Regency.​ This research is a type of quantitative descriptive research with a simple linear regression analysis approach. This research collected data using observation, questionnaires and documentation. The population of this research was all class VIII students of SMP Negeri 2 Ampek Nagari, totaling 154 people. The sampling technique used purposive sampling technique as many as 40 people. The instrument used is the questionnaire. Data analysis using percents technique. The results of this study reveal that R Square X to Y is 0.60, so it has an effect of X on Y, namely 60%, the remaining 60% is influenced by other variables that are not visible in this study. Judging from the t count of 1.558 and t table of -3.01 with (α) = 0.05. provisions t table obtained from table t. So it is concluded that the regression coefficient X on Y is significant because tcount > ttable (1.558> -3.01) then the hypothesis is accepted which says there is a significant influence of online game addiction variables on learning concentration.